SMART BILLING FOR SMART VILLAGE: INTEGRATING WHATSAPP GATEWAY AND QRIS TO STRENGTHEN BUMDES FINANCIAL MANAGEMENT IN TEGALWERU VILLAGE - Rofiq, Ainur; Prameka, Adelia Shabrina; Fasieh, Muhammad Fajrul Islam (Erudio Journal of Educational Innovation, 2025)
This community service program aims to increase compliance among the residents of Tegalweru Village in paying water and sanitation fees through the innovation of the Smart Billing digital payment system based on WhatsApp Gateway and QRIS Payment Gateway. The activity will be held on September 21, 2025, at the Tegalweru Village Hall, involving 30 participants from the Karang Taruna and BUMDes management. The implementation method uses a participatory approach through the stages of socialisation, Focus Group Discussion, training, and mentoring. The evaluation results showed a significant improvement in participants' knowledge, attitudes, and skills; with the majority of participants understanding and being able to use the digital payment system independently. This program has proven to improve the financial efficiency and transparency of BUMDes and strengthen the digital literacy of rural communities. The recommended activity is to expand the implementation of the Smart Billing system to all village residents and make it a replication model for other villages towards sustainable Smart Villages.